MCK SEBAGAI PRORITAS UTAMA DALAM KESEHATAN KELUARGA - Hidayanto, Fajar (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
MCK is a room where someone can shower to cleanse the body. Cleanliness family centered MCK, makes MCK’s cleanliness is really important. MCK in poor hygiene system will invite many germs grow and eventually create risk of germs and living environment becomes unhealthy. Observations by author at Dukuh Jati, Desa Gerbosari, Kulon Progo, Yogyakarta found that there are still many people who do not care about the cleanliness of its MCK. Therefore, the authors took the initiative to provide education about healthy MCK. With hope, Dukuh Teak be concerned with the cleanliness of its toilets.